2005
DOI: 10.1002/jssc.200401938
|View full text |Cite
|
Sign up to set email alerts
|

Surface derivatization of poly(p‐phenylene terephthalamide) fiber designed for novel separation and extraction media

Abstract: The surface derivatization of poly(p-phenylene terephthalamide) fiber was studied. The obtained surface-derivatized filaments were packed into a fused-silica capillary to evaluate its surface characteristics by using GC. As the stationary phase for GC the surface-derivatized fibers showed higher retention for alkanes and alkylbenzenes than that with the untreated Kevlar fiber. The improvements on the retention power and the peak shape were observed on the benzyl-modified fibrous stationary phase. The derivatiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 36 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…The fibrous materials could be further applied to microscale sample preparation as the extraction media. More extensive studies, including more precise control of the column temperature, theoretical prediction of the retention during temperature-programmed elution, 14,46 and the development of other polymer-coated fiber-packed materials, [47][48][49] are currently being investigated in our laboratory, including the employment of these fibrous materials as an extraction medium in a miniaturized sample preparation technique.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrous materials could be further applied to microscale sample preparation as the extraction media. More extensive studies, including more precise control of the column temperature, theoretical prediction of the retention during temperature-programmed elution, 14,46 and the development of other polymer-coated fiber-packed materials, [47][48][49] are currently being investigated in our laboratory, including the employment of these fibrous materials as an extraction medium in a miniaturized sample preparation technique.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we attempted to derivatize the surfaces of PPTA fibers in order to develop a fiber packed column. It has already been reported that the addition of other functional groups onto the nitrogen atoms contained in the amide groups can be carried out by chemical derivatization [29,30]. Additionally, it has been confirmed that the separation characteristics of the fibrous stationary phase can be tuned by changing the functional group on the surface of the PPTA fiber [30].…”
Section: Originalmentioning
confidence: 83%
“…Surface derivatization was conducted using a similar scheme as reported previously [29]. The reaction scheme is illustrated in Figure 1.…”
Section: Surface Derivatization Of Ppta Fibersmentioning
confidence: 99%
“…In order to further enhance the compatibility of the coating materials and the fiber surface, surface modification reactions of the filaments were studied. The preliminary experiments clearly demonstrated a successful surface modification of the filaments with several types of functional groups [50][51][52], although these reaction conditions should be further optimized to realize a novel stationary phase.…”
Section: Fibrous Stationary Phase In Microscale Separationsmentioning
confidence: 99%